Preventing Youth Violence: Rethinking the Role of Gender in Schools - Sundaram, Vanita (Palgrave Macmillan, 2020)
Young people explain, excuse and justify violence in a range of situations and view violence prevention as a difficult, if not impossible, endeavour. But how do young people form these views, and how can this knowledge be used by schools to reduce youth violence? This book explores these questions in a study with British teenagers